Basic optokinetic-ocular reflex pathways in the frog - Cochran, SL (J Neurosci, 1984)
Frogs (Rana temporaria) have two midbrain nuclei that receive contralateral retinal afferents, and whose neurons respond to optokinetic stimulation. The basal optic nucleus is composed of direction-selective neurons with different response types. One type is activated exclusively by upward moving optokinetic targets; another type is activated only by downward moving targets. Two other types of basal optic neurons show this vertical preference, but each is also activated by patterns moved horizontally from the nasal to temporal visual field. No activation of these cells was found with patterns moved horizontally from the temporal to nasal visual fields. Rather, cells in a discrete pretectal region have this type of sensitivity: they increase their resting rate with temporal to nasal stimulation and decrease it with nasotemporal stimulation. Oculomotor neurons (antidromically identified) have similar optokinetic sensitivities. As with basal optic neurons, these cells have exclusively upward or downward sensitivity, and some also have nasotemporal sensitivity. An additional type of oculomotor neuron and abducens motoneurons are activated by temporonasal pattern movement. In general, the extraocular motoneurons have similar velocity and pattern size preferences, as have the sensory nuclei. Investigations of the connectivity between the sensory and motor nuclei were primarily restricted to the relation between the pretectum and the abducens. A monosynaptic connection between the pretectum and the abducens is suggested by four points: (1) excitatory postsynaptic potential onset latency in antidromically identified abducens motoneurons, following optic nerve stimulation, is consistent with the interpretation of a disynaptic pathway to the abducens from the retina; (2) pretectal cells, sensitive to optokinetic stimulation, can be activated antidromically from stimulation of the abducens nucleus; (3) horseradish peroxidase injections into the pretectum result in labeling of axons, which terminate in the abducens nucleus; (4) horseradish peroxidase injections into the abducens result in labeling of cells in the pretectal region, where optokinetically sensitive cells are found. In the frog, there seem to be three-neuronal retino-ocular reflexes mediating optokinetic slow phase behavior as there are three-neuronal vestibulo-ocular reflexes that also mediate compensatory spatial behavior. It is suggested that these direct connections act to initiate ocular movements and accelerate the eye, whereas more indirect pathways may act to maintain eye position.